Self-assembling peptide hydrogels mitigate hypothermic injury during short-term storage of anchorage-dependent cell therapies - Victoria Muir; Lilith M. Caballero-Aguilar; Mandeep K. Marway; David R. Nisbet; Heather Sheardown; Ryan G. Wylie (Chemical Engineering Journal, 2026)

Serendipitous insight into pre-hatch microstructure formation in larval lake whitefish (Coregonus clupeaformis) otoliths - K. M. Dawson; M. R. Lowe; J. S. McConnell; B. A. Buechel; A. M. Muir (Environmental Biology of Fishes, 2026)

Simulating forsterite surfaces: localised chemistry and surface development under high temperatures - Joshua M. R. Muir; Yi Wang; Feiwu Zhang (Physics and Chemistry of Minerals, 2026)

Role of funders in embedding tests in conservation practice - Rebecca K. Smith; Nancy Ockendon; Nida Al‐Fulaij; Alessandro Badalotti; Rachel Beattie; James Byrne; Sophia Cooke; Tiago de Zoeten; Winifred F. Frick; Stephan M. Funk; Douglas Gibbs; Lauren Gupta; et al. (Conservation Biology, 2026)
Effective conservation practice requires decisions based on reliable and relevant evidence, but significant gaps in the evidence base exist. Incorporating well‐designed tests of the effectiveness of interventions for biodiversity in conservation projects is one of the best ways to scale up the rate of evidence generation. Funders of conservation projects are uniquely positioned to support and incentivize such tests as part of the grant‐making process. Using a structured process, as 25 conservation funders and members of Conservation Evidence, we identified means of improving the effectiveness of the work funded through the support of enhanced evidence generation. We identified 11 approaches through which funders can support embedding testing, ranging from encouraging inclusion of a test in the project proposal, to designating separate funds for incorporating a test, to supporting an external testing unit to provide training and advice. The appropriate approaches vary depending on the scale, process, and type of funding. Barriers to supporting testing and potential solutions were discussed, barriers such as a lack of skills to check tests are appropriate and well designed and the additional time needed to develop, implement, and see outcomes of tests and differing types of projects. By encouraging testing of actions as part of conservation practice (where appropriate), funders will ultimately facilitate a stronger evidence base for more effective decision‐making and better outcomes for nature and society.

Genomic signatures of adaptive divergence among lake trout (Salvelinus namaycush) ecomorphotypes - Seth R. Smith; Gordon Luikart; Andrew M. Muir; Kim T. Scribner (Conservation Genetics, 2026)

Mathematical descriptions of grading linked with prediction of mechanical consequences of suffusion - Shijin Li; Adrian R. Russell; David Muir Wood (Computers and Geotechnics, 2026)

The fate of boron isotopes in olivine after serpentine dehydration and fluid exposure - Joshua M. R. Muir; Jan C. M. de Hoog; FeiXiang Liu; Qi Liu; Feiwu Zhang (Contributions to Mineralogy and Petrology, 2025)

Nonlinear variation of structural, thermodynamic and elastic properties of Mg2SiO4-ringwoodite caused by cation disorder - Xuwei Zhao; Joshua M. R. Muir; Zhigang Zhang; Yining Zhang; Xi Liu (Physics and Chemistry of Minerals, 2025)

Quantification of the difference in hounsfield units of an electron density phantom between a conventional and standing computed tomography machine - Catherine Beck; Ashleigh V. Morrice-West; Peter Muir; Peta L. Hitchens; R. Christopher Whitton (Veterinary Research Communications, 2025)
In human CT imaging, opportunistic calculation of bone mineral density (BMD) is used to screen for osteoporosis, where BMD is estimated by Hounsfield Units (HU). There is potential to use HU for estimation of BMD in veterinary imaging. However, HU values can vary between different machines and over time. We undertook a serial measurements study to determine (1) the extent of the difference of the mean HU and noise (HU standard deviation) of eight regions of interest (ROI) of an electron density phantom scanned on two CT machines, a Siemens CT (conventional) machine and the Equina by Asto CT (standing) machine; and (2) to determine if the HU values obtained on each machine differed over time. The mean HU from 30 scans of an electron density phantom were generated from each of the two CT machines ( N = 60; conventional and standing). Differences between machines were assessed using a linear mixed effects model. The mean HU of each positive value ROI from the conventional machine was decreased compared with the standing machine ( P < 0.001) and the difference was greatest for the denser phantom inserts. A calibration curve equation utilising the four bone-equivalent insert plugs of the phantom, with known calcium hydroxyapatite (CaHA) concentration, was generated using linear regression to represent CaHA, and therefore BMD, for the conventional machine (CaHA = -29.58 + 0.98xROI mean ) and the standing machine (CaHA = -54.53 + 0.95xROI mean ). For opportunistic calculation of BMD from HU in horses, the differences in HU observed between different CT machines warrants calibration of HU using a bone equivalent phantom.

Total knee replacement in a dog with an articular epiphyseal medial condylar fracture of the distal femur, a case report - Brent R. Fink; Laurent P. Guiot; Peter Muir (Veterinary Research Communications, 2025)

Designing Sortable Guilds for Multispecies Selective Fish Passage - David M. Benoit; Daniel P. Zielinski; Reid G. Swanson; Donald A. Jackson; Robert L. McLaughlin; Theodore R. Castro‐Santos; R. Andrew Goodwin; Thomas C. Pratt; Andrew M. Muir (Fish and Fisheries, 2025)
The importance of connectivity for freshwater organisms is widely recognised, yet in‐stream barriers associated with population declines and increased risk of extinction remain globally ubiquitous. Despite their negative consequences, these barriers can protect aquatic communities by limiting the spread of invasive species, leading to conflicting management goals in some regions. Selective fish passage is a solution for the conflicting goals of passing native, desirable species while restricting the spread of invasives. Approaches that can target groups of species sharing similar attributes (i.e. guilds) are likely to be more efficient than those that target species individually, particularly in taxonomically diverse systems. We explored the guild structure of 220 Great Lakes freshwater fishes based on morphological, phenological, physiological and behavioural attributes associated with passage and movement. We identified five distinct guilds as well as the attributes most important for defining these groupings: maximum total length, trophic level, relative eye size, spawning temperature, spawning season, presence/absence of ampullary electroreceptors and the presence/absence of hearing specialisations. The approaches outlined in this work can be generalised to enhance selective fish passage in aquatic ecosystems worldwide.

Challenges in assessing the effects of environmental governance systems on conservation outcomes - Raphael A. Ayambire; Trina Rytwinski; Jessica J. Taylor; Matthew W. Luizza; Matthew J. Muir; Cynthia Cadet; Derek Armitage; Nathan J. Bennett; Jeremy Brooks; Samantha H. Cheng; Jenny Martinez; Meenakshi Nagendran; et al. (Conservation Biology, 2025)
Effective governance is crucial for the success of conservation projects aimed at protecting wildlife populations and supporting human well‐being. However, few large‐scale, comprehensive syntheses have been conducted on the effects of different environmental governance types on conservation outcomes (i.e., biological and ecological effectiveness or effects of conservation on human well‐being), and clarity on the quantity and quality of evidence remains dispersed and ambiguous. We attempted a systematic map of the evidence on the effectiveness of different governance types to meet desired conservation outcomes in Africa, Asia, and Latin America. However, early in this effort, we observed a general lack of empirical research on the links between governance and conservation outcomes. To fill observed data gaps in the evidence base, we tried triangulating governance data from alternative sources (Protected Planet database) and pooling evidence from research conducted within the same conservation areas. Limited data were contained in the Protected Planet database, and governance types in conservation areas and landscapes were complex, making it difficult to use these approaches to assign governance types to conservation areas. To illustrate our observations from the failed systematic map attempt, we prepared a rapid evidence map that outlines a subset of the evidence base of articles linking governance types and governance principles with conservation outcomes. Only 3.2% (34 of 1067) of the articles we screened directly related conservation outcomes to governance type, and even fewer related governance principles to conservation outcomes. Based on our findings, we recommend improving the evidence base by supporting empirical research and increasing the availability and quality of governance data in freely accessible databases. These recommendations are critical for enhancing understanding of the role of governance in conservation projects and improving conservation outcomes.

Practices, events, and effects: Improving causal analysis with the geographic information from cultural mapping in Canada - Bruce R. Muir (Environmental Impact Assessment Review, 2025)

Self-aggregation for sustainable harvesting of microalgae - Emma Muir; Arthur R. Grossman; Yusuf Chisti; Bruno Fedrizzi; Benoit Guieysse; Maxence Plouviez (Algal Research, 2024)

Historical cisco Coregonus artedi population collapses in Green Bay, Lake Michigan, and Saginaw Bay, Lake Huron, during the 1950s - Benjamin J. Rook; Yu‐Chun Kao; Randy L. Eshenroder; Charles R. Bronte; Andrew M. Muir (Fisheries Management and Ecology, 2024)
Coregonus populations across their Holarctic range have often undergone unexplained collapses. Here, we document causes of collapse for two of the largest Coregonus populations in the world, cisco ( C. artedi ) in Green Bay, Lake Michigan, and Saginaw Bay, Lake Huron, during the 1950s. We used simulation models, rank‐order correlations, and historical literature to evaluate effects of overfishing, interactions with introduced rainbow smelt ( Osmerus mordax ), and overwinter bottom hypoxia on both cisco populations. Fully selected exploitation rates for cisco were alarmingly high (0.82–0.84), correlations and anecdotal evidence suggested negative interactions with rainbow smelt, and extensive areas of hypoxia coincident with cisco declines suggested incubation of cisco embryos was impaired regionally. Our findings suggested that negative effects of rainbow smelt were mainly responsible for the cisco population collapse in Green Bay and that overfishing and hypoxia had suppressed the Saginaw Bay cisco population before rainbow smelt caused its final collapse.

The antimicrobial efficacy of native Australian essential oils in liquid and vapour phase against foodborne pathogens and spoilage microorganisms - A.R. Mukurumbira; R.A. Shellie; R. Keast; E.A. Palombo; B.W. Muir; S.R. Jadhav (Food Control, 2023)

Machine Learning–Based Identification of Target Groups for Thrombectomy in Acute Stroke - Fanny Quandt; Fabian Flottmann; Vince I. Madai; Anna Alegiani; Clemens Küpper; Lars Kellert; Adam Hilbert; Dietmar Frey; Thomas Liebig; Jens Fiehler; Mayank Goyal; Jeffrey L. Saver; et al. (Translational Stroke Research, 2023)
Whether endovascular thrombectomy (EVT) improves functional outcome in patients with large-vessel occlusion (LVO) stroke that do not comply with inclusion criteria of randomized controlled trials (RCTs) but that are considered for EVT in clinical practice is uncertain. We aimed to systematically identify patients with LVO stroke underrepresented in RCTs who might benefit from EVT. Following the premises that (i) patients without reperfusion after EVT represent a non-treated control group and (ii) the level of reperfusion affects outcome in patients with benefit from EVT but not in patients without treatment benefit, we systematically assessed the importance of reperfusion level on functional outcome prediction using machine learning in patients with LVO stroke treated with EVT in clinical practice ( N = 5235, German-Stroke-Registry) and in patients treated with EVT or best medical management from RCTs ( N = 1488, Virtual-International-Stroke-Trials-Archive). The importance of reperfusion level on outcome prediction in an RCT-like real-world cohort equaled the importance of EVT treatment allocation for outcome prediction in RCT data and was higher compared to an unselected real-world population. The importance of reperfusion level was magnified in patient groups underrepresented in RCTs, including patients with lower NIHSS scores (0–10), M2 occlusions, and lower ASPECTS (0–5 and 6–8). Reperfusion level was equally important in patients with vertebrobasilar as with anterior LVO stroke. The importance of reperfusion level for outcome prediction identifies patient target groups who likely benefit from EVT, including vertebrobasilar stroke patients and among patients underrepresented in RCT patients with low NIHSS scores, low ASPECTS, and M2 occlusions.

Comprehensive screening and characterization of polyphenol compounds from pasture grasses used for livestock production under temperate region - BK Amrit; Eric N. Ponnampalam; Sonu Macwan; Hanjing Wu; Ahsan Aziz; Stephanie Muir; Frank R. Dunshea; Hafiz A.R. Suleria (Animal Feed Science and Technology, 2023)

What is a fish? The life and legend of David L.G. Noakes - Lynn D. Bouvier; Jeffrey R. Baylis; Anders Klemetsen; Bjarni K. Kristjánsson; Judith L. Li; Pierre Magnan; Robert L. McLaughlin; Andrew M. Muir; Yoshitaka Sakakura; Skúli Skúlason (Environmental Biology of Fishes, 2023)
David Lloyd George Noakes (1942–2020) is best known for his insatiable curiosity, his quick wit and dry sense of humor, his scientific contributions to the field of animal behaviour, and his ability to form and maintain long-lasting connections. His research interests were vast but remained grounded in early life history, behaviour, social behaviour, the evolution of behaviour, behavioural genetics, and evolutionary ecology. David had a remarkable ability to establish and maintain strong connections within the international academic community. David was also internationally recognized for his numerous contributions as a scientific editor, promoting accessibility to the international community that he served. We memorialize David’s legacy in this tribute article, ensuring that his accomplishments and the momentous impact he had on the scientific community are not soon forgotten.

On the relevance of animal behavior to the management and conservation of fishes and fisheries - Steven J. Cooke; Heather L. Auld; Kim Birnie-Gauvin; Chris K. Elvidge; Morgan L. Piczak; William M. Twardek; Graham D. Raby; Jacob W. Brownscombe; Jonathan D. Midwood; Robert J. Lennox; Christine Madliger; Alexander D. M. Wilson; et al. (Environmental Biology of Fishes, 2023)

Funding evidence‐based conservation - Danni Parks; Nida Al‐Fulaij; Clare Brook; Stuart H. M. Butchart; Jean‐Gaël Collomb; David Cope; Simon Dowell; Becky Falkingham; Winifred F. Frick; Douglas Gibbs; Emily E. Gray; Nicolas Heard; et al. (Conservation Biology, 2022)

Development and Diversification of Sugar Beet in Europe - B. M. Muir; A. R. Anderson (Sugar Tech, 2022)

Fast anisotropic Mg and H diffusion in wet forsterite - Joshua M. R. Muir; Feiwu Zhang; Andrew M. Walker (Physics and Chemistry of Minerals, 2022)

Controls on the distribution of hydrous defects in forsterite from a thermodynamic model - Joshua M. R. Muir; Michael Jollands; Feiwu Zhang; Andrew M. Walker (Physics and Chemistry of Minerals, 2022)

High regional and intrageneric variation in susceptibility to mass bleaching in Indo‐Pacific coral species - Paul R. Muir; Terence Done; J. David Aguirre (Global Ecology and Biogeography, 2021)
Aim We investigate how susceptibility to mass bleaching varies between closely related coral species, and the validity of applying these susceptibility data (at the appropriate taxonomic level) across geographical regions. We also conduct a preliminary analysis of factors likely to affect geographical variability and examine which data are required for adequate assessment of the risk to species and regional populations from repeated mass bleaching events. Location Twenty‐two sites in the central Great Barrier Reef, Australia (GBR) and 30 sites in the central Maldives Archipelago (MA). Time period 2002 for the GBR and 2016 for the MA. Major taxa studied Corals (order Scleractinia). Methods After marine heat‐wave conditions, timed in situ surveys recorded bleaching responses of 7,368 coral colonies exposed to similar levels of temperature stress at a similar depth of occurrence and with similar subsequent mortality. In each region, a separate phylogenetic mixed model was used to estimate deep‐time phylogenetic‐, contemporary‐ (indicative of recent adaptation/acclimatization) and local‐scale effects. The results were compared between regions in relative terms as a hierarchy of species susceptibilities. Results Susceptibility varied widely between regions: 27 of 106 species analysed were in the same quartile for relative susceptibility in both regions. Closely related species varied widely in their individual susceptibilities. Phylogenetic effects were moderate in both regions, but greater contemporary effects in the MA suggested recent evolution and acclimatization, consistent with a stronger history of recent bleaching events. Main conclusions The high regional and intrageneric variation in susceptibility to bleaching described here suggests that there might be important differences in the extent to which these Indian and Pacific Ocean coral populations are exhibiting responses to deep‐time evolutionary changes, on the one hand, versus recent adaptation, on the other. We reveal a concerning lack of regional‐scale data identifying species most at risk from this, the greatest current threat to coral reefs.

Explaining the dependence of M-site diffusion in forsterite on silica activity: a density functional theory approach - Joshua M. R. Muir; Michael Jollands; Feiwu Zhang; Andrew M. Walker (Physics and Chemistry of Minerals, 2020)
Experimentally, silica activity (aSiO 2 ) has been shown to have an effect on Mg diffusion in forsterite, but no fully satisfactory mechanism has yet been proposed. We calculated the effects of aSiO 2 and aluminium content (the main contaminant in some recent experimental studies), and their co-effect, on Mg diffusion in forsterite, using thermodynamic minimisations of defect formation energies [calculated using density functional theory (DFT)] and a Monte-Carlo diffusion model. These two variables, in isolation, do not appreciably change the defect concentrations of forsterite and thus do not affect the diffusivity of Mg. However, when elevated together, they cause large increases in the Mg vacancy content and thus can increase the Mg diffusivity by one to six orders of magnitude depending on temperature, with little pressure dependence. This effect is largely independent of Al 2 O 3 concentration above ~ 1 wt. ppm, and thus, for all practical purposes, should occur wherever forsterite is in the presence of enstatite. It is also largely dependent upon configurational entropy and is thus highly sensitive to the chemistry of the crystal. A low concentration of structurally bound hydroxyl groups at low temperatures (1000 K) suppresses this effect in pure forsterite, but it is likely robust in the presence of water either when alternative water sinks (such as Ti or Fe) are present, or at high temperatures (> 1500 K). This effect is also robust in the presence of ferrous iron (or other substitutional Mg defects) at all temperatures. Fe 2 O 3 can operate like Al 2 O 3 in this reaction and should enhance its effect. These findings explain the experimentally observed dependency of Mg diffusion of aSiO 2 , and elucidate how chemical activity variations in both experiments and natural settings could affect not only the diffusivity of Mg in forsterite, but of olivine-hosted cations in general.

Temporal Trends in Polybrominated Diphenylethers (PBDEs) in Blubber of Ringed Seals (Pusa hispida) from Ulukhaktok, NT, Canada Between 1981 and 2015 - R. F. Addison; D. C. G. Muir; M. G. Ikonomou; C. Dubetz; T. G. Smith; J. Alikamik (Archives of Environmental Contamination and Toxicology, 2020)

Brown bullhead at the St. Lawrence River (Cornwall) Area of Concern: health and endocrine status in the context of tissue concentrations of PCBs and mercury - M. D. O. Pinheiro; D. B. D. Simmons; M. Villella; G. R. Tetreault; D. C. G. Muir; M. E. McMaster; L. M. Hewitt; J. L. Parrott; B. J. Park; S. B. Brown; J. P. Sherry (Environmental Monitoring and Assessment, 2020)

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Nutritional evaluation and productivity of supplemented sheep grazing in semiarid rangeland of northeastern Brazil - A. R. Araújo; N. M. Rodriguez; Marcos Cláudio Pinheiro Rogério; I. Borges; E. O. S. Saliba; S. A. Santos; R. C. F. F. Pompeu; F. E. P. Fernandes; J. P. Monteiro; J. P. Muir (Tropical Animal Health and Production, 2019)

Acropora tenella, a zooxanthellate coral extending to 110-m depth in the northern Coral Sea - P. R. Muir; M. Pichon; L. Squire; C. C. Wallace (Marine Biodiversity, 2019)

Role of Macrophage Dopamine Receptors in Mediating Cytokine Production: Implications for Neuroinflammation in the Context of HIV-Associated Neurocognitive Disorders - R. A. Nolan; R. Muir; K. Runner; E. K. Haddad; P. J. Gaskill (Journal of Neuroimmune Pharmacology, 2019)

Tropical cyclogenesis in warm climates simulated by a cloud-system resolving model - Alexey V. Fedorov; Les Muir; William R. Boos; Joshua Studholme (Climate Dynamics, 2019)

Review of non-clinical risk models to aid prevention of breast cancer - Kawthar Al-Ajmi; Artitaya Lophatananon; Martin Yuille; William Ollier; Kenneth R. Muir (Cancer Causes & Control, 2018)

Effects of urbanization on the population structure of freshwater turtles across the United States - David R. Bowne; Bradley J. Cosentino; Laurel J. Anderson; Christopher P. Bloch; Sandra Cooke; Patrick W. Crumrine; Jason Dallas; Alexandra Doran; Jerald J. Dosch; Daniel L. Druckenbrod; Richard D. Durtsche; Danielle Garneau; et al. (Conservation Biology, 2018)
Landscape‐scale alterations that accompany urbanization may negatively affect the population structure of wildlife species such as freshwater turtles. Changes to nesting sites and higher mortality rates due to vehicular collisions and increased predator populations may particularly affect immature turtles and mature female turtles. We hypothesized that the proportions of adult female and immature turtles in a population will negatively correlate with landscape urbanization. As a collaborative effort of the Ecological Research as Education Network (EREN), we sampled freshwater turtle populations in 11 states across the central and eastern United States. Contrary to expectations, we found a significant positive relationship between proportions of mature female painted turtles ( Chrysemys picta ) and urbanization. We did not detect a relationship between urbanization and proportions of immature turtles. Urbanization may alter the thermal environment of nesting sites such that more females are produced as urbanization increases. Our approach of creating a collaborative network of scientists and students at undergraduate institutions proved valuable in terms of testing our hypothesis over a large spatial scale while also allowing students to gain hands‐on experience in conservation science.

FDC:TFH Interactions within Cervical Lymph Nodes of SIV-Infected Rhesus Macaques - Rajnish S. Dave; Ravi K. Sharma; Roshell R. Muir; Elias Haddad; Sanjeev Gumber; Francois Villinger; Artinder P. Nehra; Zafar K. Khan; Brian Wigdahl; Aftab A. Ansari; Siddappa N. Byrareddy; Pooja Jain (Journal of Neuroimmune Pharmacology, 2018)

Small-scale intraspecific patterns of adaptive immunogenetic polymorphisms and neutral variation in Lake Superior lake trout - Shauna M. Baillie; Riley R. Hemstock; Andrew M. Muir; Charles C. Krueger; Paul Bentzen (Immunogenetics, 2018)

Islands in the ice stream: were spawning habitats for native salmonids in the Great Lakes created by paleo‐ice streams? - Stephen C Riley; Thomas R Binder; Taaja R Tucker; John Menzies; Nick Eyles; John Janssen; Andrew M Muir; Peter C Esselman; Nigel J Wattrus; Charles C Krueger (Fish and Fisheries, 2017)
Lake trout Salvelinus namaycush , lake whitefish Coregonus clupeaformis and cisco Coregonus artedi are salmonid fishes native to the Laurentian Great Lakes that spawn on rocky substrates in the fall and early winter. After comparing the locations of spawning habitat for these species in the main basin of Lake Huron with surficial substrates and the hypothesized locations of fast‐flowing Late Wisconsinan paleo‐ice streams, we hypothesize that much of the spawning habitat for these species in Lake Huron is the result of deposition and erosion by paleo‐ice streams. This hypothesis may represent a new framework for the identification and protection of spawning habitat for these native species, some of which are currently rare or extirpated in some of the Great Lakes. We further suggest that paleo‐ice streams may have been responsible for the creation of native salmonid spawning habitat elsewhere in the Great Lakes and in other glaciated landscapes.

A rare ‘deep-water’ coral assemblage in a shallow lagoon in Micronesia - Paul R. Muir; Carden C. Wallace (Marine Biodiversity, 2016)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

ESA ice sheet CCI: derivation of the optimal method for surface elevation change detection of the Greenland ice sheet – round robin results - J.F. Levinsen; K. Khvorostovsky; F. Ticconi; A. Shepherd; R. Forsberg; L.S. Sørensen; A. Muir; N. Pie; D. Felikson; T. Flament; R. Hurkmans; G. Moholdt; et al. (International Journal of Remote Sensing, 2015)

New insight into the spawning behavior of lake trout, Salvelinus namaycush, from a recovering population in the Laurentian Great Lakes - T. R. Binder; H. T. Thompson; A. M. Muir; S. C. Riley; J. E. Marsden; C. R. Bronte; C. C. Krueger (Environmental Biology of Fishes, 2015)

Nitrogen uptake dynamics of a persistent cyanobacterium Cyanothece sp. bloom in Lake St Lucia, South Africa - SJ du Plooy; AJ Smit; R Perissinotto; DG Muir (African Journal of Marine Science, 2014)

Local adaptation with high gene flow: temperature parameters drive adaptation to altitude in the common frog ( R ana temporaria ) - A. P. Muir; R. Biek; R. Thomas; B. K. Mable (Molecular Ecology, 2014)
Both environmental and genetic influences can result in phenotypic variation. Quantifying the relative contributions of local adaptation and phenotypic plasticity to phenotypes is key to understanding the effect of environmental variation on populations. Identifying the selective pressures that drive divergence is an important, but often lacking, next step. High gene flow between high‐ and low‐altitude common frog ( R ana temporaria ) breeding sites has previously been demonstrated in Scotland. The aim of this study was to assess whether local adaptation occurs in the face of high gene flow and to identify potential environmental selection pressures that drive adaptation. Phenotypic variation in larval traits was quantified in R . temporaria from paired high‐ and low‐altitude sites using three common temperature treatments. Local adaptation was assessed using Q ST – F ST analyses, and quantitative phenotypic divergence was related to environmental parameters using Mantel tests. Although evidence of local adaptation was found for all traits measured, only variation in larval period and growth rate was consistent with adaptation to altitude. Moreover, this was only evident in the three mountains with the highest high‐altitude sites. This variation was correlated with mean summer and winter temperatures, suggesting that temperature parameters are potentially strong selective pressures maintaining local adaptation, despite high gene flow.

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Implications of CMIP3 model biases and uncertainties for climate projections in the western tropical Pacific - Jaclyn N. Brown; Alex Sen Gupta; Josephine R. Brown; Les C. Muir; James S. Risbey; Penny Whetton; Xuebin Zhang; Alexandre Ganachaud; Brad Murphy; Susan E. Wijffels (Climatic Change, 2013)

Using genetic variation to infer associations with climate in the common frog, R ana temporaria - A. P. Muir; R. Thomas; R. Biek; B. K. Mable (Molecular Ecology, 2013)
Recent and historical species' associations with climate can be inferred using molecular markers. This knowledge of population and species‐level responses to climatic variables can then be used to predict the potential consequences of ongoing climate change. The aim of this study was to predict responses of Rana temporaria to environmental change in Scotland by inferring historical and contemporary patterns of gene flow in relation to current variation in local thermal conditions. We first inferred colonization patterns within Europe following the last glacial maximum by combining new and previously published mitochondrial DNA sequences. We found that sequences from our Scottish samples were identical to (92%), or clustered with, the common haplotype previously identified from Western Europe. This clade showed very low mitochondrial variation, which did not allow inference of historical colonization routes but did allow interpretation of patterns of current fine‐scale population structure without consideration of confounding historical variation. Second, we assessed fine‐scale microsatellite‐based patterns of genetic variation in relation to current altitudinal temperature gradients. No population structure was found within altitudinal gradients (average F ST = 0.02), despite a mean annual temperature difference of 4.5 °C between low‐ and high‐altitude sites. Levels of genetic diversity were considerable and did not vary between sites. The panmictic population structure observed, even along temperature gradients, is a potentially positive sign for R. temporaria persistence in Scotland in the face of a changing climate. This study demonstrates that within taxonomic groups, thought to be at high risk from environmental change, levels of vulnerability can vary, even within species.

Soil biotransformation of thiodiglycol, the hydrolysis product of mustard gas: understanding the factors governing remediation of mustard gas contaminated soil - Hong Li; Robert Muir; Neil R. McFarlane; Richard J. Soilleux; Xiaohong Yu; Ian P. Thompson; Simon A. Jackman (Biodegradation, 2013)

An environmental justice analysis of caribou recovery planning, protection of an Indigenous culture, and coal mining development in northeast British Columbia, Canada - Bruce R. Muir; Annie L. Booth (Environment, Development and Sustainability, 2012)

Diversity of Scleractinia and Octocorallia in the mesophotic zone of the Great Barrier Reef, Australia - T. C. L. Bridge; K. E. Fabricius; P. Bongaerts; C. C. Wallace; P. R. Muir; T. J. Done; J. M. Webster (Coral Reefs, 2012)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Mesophotic coral ecosystems on the walls of Coral Sea atolls - P. Bongaerts; T. C. L. Bridge; D. I. Kline; P. R. Muir; C. C. Wallace; R. J. Beaman; O. Hoegh-Guldberg (Coral Reefs, 2011)

Linkage to chromosome 2q32.2-q33.3 in familial serrated neoplasia (Jass syndrome) - Aedan Roberts; Derek Nancarrow; Mark Clendenning; Daniel D. Buchanan; Mark A. Jenkins; David Duggan; Darin Taverna; Diane McKeone; Rhiannon Walters; Michael D. Walsh; Bruce W. Young; Jeremy R. Jass; et al. (Familial Cancer, 2011)

Numerical Modelling of a Shaking Table Test for Soil-Foundation-Superstructure Interaction by Means of a Soil Constitutive Model Implemented in a FEM Code - G. Abate; M. R. Massimino; M. Maugeri; D. Muir Wood (Geotechnical and Geological Engineering, 2010)

Chromosome abnormalities, mental retardation and the search for genes in bipolar disorder and schizophrenia - D. H. R. Blackwood; T. Thiagarajah; P. Malloy; B. S. Pickard; W. J. Muir (Neurotoxicity Research, 2008)

Islands under islands: The phylogeography and evolution of Halocaridina rubra Holthuis, 1963 (Crustacean: Decapoda: Atyidae) in the Hawaiian archipelago - Jonathan D. Craft; Atlantis D. Russ; Mike N. Yamamoto; Thomas Y. Iwai; Skippy Hau; John Kahiapo; Charlie T. Chong; Sharon Ziegler-Chong; Cam Muir; Yoshihisa Fujita; Dan A. Polhemus; Robert A. Kinzie; et al. (Limnology and Oceanography, 2008)
The genetic structure and evolutionary history of an endemic anchialine species, the shrimp Halocaridina rubra Holthuis, 1963 (Crustacean: Decapoda: Atyidae), was investigated across its range in the Hawaiian archipelago using mitochondrial (e.g., cytochrome oxidase subunit I and large subunit ribosomal) gene sequences. A survey of 573 individuals collected from 34 sites on the islands of Hawai’i, Maui, and Oahu revealed 13 distinct genetic groups belonging to eight divergent lineages. In general, a Halocaridina genetic group or lineage was restricted to a particular region of a single Hawaiian Island, with no individuals being exchanged between them. This pattern stems from a combination of intrinsic organismal properties such as large egg size, abbreviated development, restricted larval habitat and larval feeding mode, and extrinsic obstacles to gene flow in the form of a marine barrier and geologic features that compartmentalize the islands' aquifers. The phylogeographic structuring on and between islands suggests that evolutionary diversification in Halocaridina is driven by population fragmentation, isolation, and subsequent diversification in the aquifers of the Hawaiian Islands. Calibration of cytochrome oxidase subunit I sequence divergence between sister Halocaridina lineages to the geologic age of Kilauea volcano on Hawai'i implies that diversification in the genus is proceeding at a short‐term rate of 20% per million years. The examined mitochondrial genes were generally inadequate for inferring phylogenetic relationships between the Halocaridina lineages.

Recognition of separate genera within Acropora based on new morphological, reproductive and genetic evidence from Acropora togianensis, and elevation of the subgenus Isopora Studer, 1878 to genus (Scleractinia: Astrocoeniidae; Acroporidae) - C. C. Wallace; C. A. Chen; H. Fukami; P. R. Muir (Coral Reefs, 2007)

Post-bleaching renewal of the dominant reef-building coral Acropora abrotanoides in the Lakshadweep islands of India - Carden C. Wallace; M. Venkatesh; Paul R. Muir (Coral Reefs, 2007)

Are some genetic risk factors common to schizophrenia, bipolar disorder and depression? evidence fromDISC1, GRIK4 andNRG1 - Douglas H. R. Blackwood; Ben J. Pickard; Pippa A. Thomson; Kathryn L. Evans; David J. Porteous; Walter J. Muir (Neurotoxicity Research, 2007)

Clinical phenotypes associated with DISC1, a candidate gene for schizophrenia - D. H. R. Blackwood; W. J. Muir (Neurotoxicity Research, 2004)

Seasonality of arbuscular mycorrhizal hyphae and glomalin in a western Montana grassland - Emily R. Lutgen; Deborah Muir-Clairmont; Jon Graham; Matthias C. Rillig (Plant and Soil, 2003)

Laboratory Evaluation of the Toxicity of Perfluorooctane Sulfonate (PFOS) on Selenastrum capricornutum , Chlorella vulgaris , Lemna gibba , Daphnia magna , and Daphnia pulicaria - T. M. Boudreau; P. K. Sibley; S. A. Mabury; D. G. C. Muir; K. R. Solomon (Archives of Environmental Contamination and Toxicology, 2003)

Global Distribution of Halogenated Dimethyl Bipyrroles in Marine Mammal Blubber - S. Tittlemier; A. Borrell; J. Duffe; P. J. Duignan; P. Fair; A. Hall; P. Hoekstra; K. M. Kovacs; M. M. Krahn; M. Lebeuf; C. Lydersen; D. Muir; et al. (Archives of Environmental Contamination and Toxicology, 2002)

Bioaccumulation of Organochlorine Contaminants in Bowhead Whales ( Balaena mysticetus ) from Barrow, Alaska - P. F. Hoekstra; T. M. O'Hara; S. J. Pallant; K. R. Solomon; D. C. G. Muir (Archives of Environmental Contamination and Toxicology, 2002)

Sealing techniques and methods of determining gastightness - M. E. Casada; R. T. Noyes; H. L. Towne; B. M. Schneider; Michelle S. Smith; R. E. Williams; R. E. Williams; S. Prabhakaran; B. M. Schneider; R. T. Noyes; J. Subbiah; J. T. Criswell; et al. (Phytoparasitica, 2001)

Isolation of nodavirus from Scottish farmed halibut, Hippoglossus hippoglossus (L). - W G Starkey; J H Ireland; K F Muir; A P Shinn; R H Richards; H W Ferguson (Journal of Fish Diseases, 2000)

Aspirin, NSAIDs and colorectal cancer—what do the epidemiological studies show and what do they tell us about the modus operandi? - K. R. Muir; R. F. A. Logan (Apoptosis, 1999)

Angular and fibrous particles in lung in relation to silica-induced diseases - A. Dufresne; R. Bégin; C. Dion; J. Jagirdar; W. N. Rom; P. Loosereewanich; D. C. F. Muir; A. C. Ritchie; G. Perrault (International Archives of Occupational and Environmental Health, 1998)

The Pharmacokinetics and Electroencephalogram Response of Remifentanil Alone and in Combination with Esmolol in the Rat - Sam H. Haidar; J. Edward Moreton; Zhongming Liang; John R Hoke; Keith T. Muir; Natalie D. Eddington (Pharmaceutical Research, 1997)

Organochlorine chemical and heavy metal contaminants in white-beaked dolphins (Lagenorhynchus albirostris) and pilot whales (Globicephala melaena) from the coast of Newfoundland, Canada - D. C. G. Muir; R. Wagemann; N. P. Grift; R. J. Norstrom; M. Simon; J. Lien (Archives of Environmental Contamination and Toxicology, 1988)

Factors affecting the exposure of ground- rig applicators to 2,4-D dimethylamine salt - R. Grover; A. J. Cessna; N. I. Muir; D. Riedel; C. A. Franklin; K. Yoshida (Archives of Environmental Contamination and Toxicology, 1986)